Mechanical and Micro Structural Analysis of Dissimilar Weld Joints - Jha, Shivani (My University, 2017)
In power generation industries, there is a wide application of joining low alloy metals to austenitic stainless steel which are known as dissimilar weldments. These dissimilar metal joint have their applications in nuclear power plants and aerospace industries due to high strength at both high and room temperature conditions. A metal joint of low alloy steel and austenitic stainless steel provides a good blend of mechanical properties, weldability and formability. The demand of dissimilar welding arises due to better performance and economic benefits. As this technique involves the metal joints whose melting points, coefficient of thermal expansion and chemical compositions are unlike. It was very well known that, severe gradients in thermal and mechanical loading were exist in boilers used in power plant industries. The parts of boiler that are headed under the low temperature zone can be made with low alloy steel and rest part is to be constructed by austenitic steel for economic reason. Those dissimilar joints having austenitic steels have very prone to unexpected phase propagation which results in major mechanical and metallurgical changes. Therefore, it is very necessary to optimize the parameters such as (arc length, current, gas flow rate, type of fillers and types of grooves) so as to develop sound weld. Hence in the present study two dissimilar metals are welded that is SS316 and SS410 using TIG welding technique. In the experiment, L18 orthogonal array is applied by varying welding parameters. Micro hardness, tensile strength, optical microscopy and scanning electron microscopy was performed on the 18 trials obtained from orthogonal array. From the fractography, mostly the ductile fracture occur from AISI 410 side and some fracture has been occurring at the mid or weld joint. The significant factors affecting the micro hardness are current, arc length and type of fillers. The micro hardness increases with the decrease in current. From the microstructures the grain coarsening, segregations, skeleton structure and vermicular structures were observed in the weld bead.
Keywords: TIG Welding, Tensile test